Homeobox A5 and C10 genes modulate adaptation of brown adipose tissue during exercise training in juvenile rats. Issue 2 (5th January 2021) - Kato, Hisashi; Ario, Takuto; Kishida, Toshiaki; Tadano, Manami; Osawa, Seita; Maeda, Yuki; Takakura, Hisashi; Izawa, Tetsuya
Abstract : New Findings: What is the central question of this study? Exercise can stimulate brown adipose tissue (BAT) with subsequent increase in uncoupling protein 1 expression and mitochondrial biogenesis. In that case, do BAT‐specific Hox genes modify BAT functioning and cause uncoupling protein expression changes due to exercise? What is the main finding and its importance? Exercise enhanced brown adipocyte markers, with significant upregulation of HoxA5 and downregulation of HoxC10 mRNA expression in rat BAT. HoxA5 and HoxC10 are thus likely to play distinct roles in exercise‐induced changes in BAT markers during the early postnatal period. These findings provide new insight into the mechanisms underlying exercise‐induced changes in BAT function. Abstract: Brown adipose tissue (BAT) recruitment is involved in increased energy expenditure associated with cold exposure and exercise training. We explored whether exercise training induced changes in expression levels of brown adipocyte‐selective factors and Homeobox ( Hox ) genes during the post‐weaning growth period of male Wistar rats. Relative to total body weight, BAT weights alone were lower in exercise‐trained (EX) rats compared to sedentary control (SED) rats. mRNA expression of HoxA5 was higher and that of HoxC10 was lower in EX rats than in SED rats, accompanied by both higher citrate synthase activity and protein expression levels for uncoupling protein 1 (UCP1), peroxisome proliferator‐activated receptor (PPAR) α, and PPARγ‐coactivator (PGC)‐1α. HoxA5 knockdown with siRNA reduced the expression of PR‐domain containing 16 ( Prdm16 ), cell death‐inducing DNA fragmentation factor‐α‐like effector A ( Cidea ) gene, type 2 deiodinase mRNA, and PRDM16 protein. Comparatively, HoxC10 knockdown with siRNA enhanced mRNA expression of Prdm16, Pparα and Pgc1α and protein expression of UCP1, PPARα and PGC1α in brown adipocytes. The stimulation of brown adipocytes with isoproterenol, a β‐adrenoceptor agonist, caused a phenomenon similar to the effect of exercise training on the genes tested: upregulation of HoxA5 mRNA, downregulation of HoxC10 mRNA, and increased protein expression for UCP1 and PGC1α. Collectively, HoxA5 and HoxC10 may have unique functions that contribute to modulating the expression of BAT‐selective markers in BAT of juvenile rats during exercise training. The study findings regarding activation and recruitment of BAT during exercise training have implications for anti‐obesity management. Abstract :